2020
DOI: 10.1177/1071100720937013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Press Ganey Satisfaction and PROMIS Function and Pain in Foot and Ankle Patients

Abstract: Background: Patient satisfaction has garnered interest as a tool to measure health care quality. However, orthopedic studies in total joint arthroplasty, spine, and hand patients have offered conflicting relationships between Press Ganey (PG) satisfaction metrics and patient-reported outcome (PRO) measures. No prior study has assessed the relationship between PG and PROs in foot and ankle patients. Whether satisfaction and outcomes instruments, though, measure similar or differing aspects of the patient experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Another study of 1,644 adolescents in Northwestern Burkina Faso (14) randomized people to a conventional verbal response arm (high social desirability bias environment) and a nonverbal response arm (low social desirability bias environment) and found significantly higher levels of reported sexual assault and forced sex in the non-verbal response (14). These findings suggest that social desirability could be part of the explanation of ceiling effects and nonparametric distributions of the current PREMs, but there are a variety of other modifiable and non-modifiable patient factors that may explain why patients are likely to give us top scores (15–23). Although it may be flattering for physicians to receive top scores, it may contribute to a false sense that there is no further opportunity for improvement.…”
Section: Discussionmentioning
confidence: 85%
“…Another study of 1,644 adolescents in Northwestern Burkina Faso (14) randomized people to a conventional verbal response arm (high social desirability bias environment) and a nonverbal response arm (low social desirability bias environment) and found significantly higher levels of reported sexual assault and forced sex in the non-verbal response (14). These findings suggest that social desirability could be part of the explanation of ceiling effects and nonparametric distributions of the current PREMs, but there are a variety of other modifiable and non-modifiable patient factors that may explain why patients are likely to give us top scores (15–23). Although it may be flattering for physicians to receive top scores, it may contribute to a false sense that there is no further opportunity for improvement.…”
Section: Discussionmentioning
confidence: 85%
“…Correlations between the 2 systems have rarely been evaluated. Nixon et al 3 found that these correlations were strikingly weak. They compared the Press Ganey survey of patient satisfaction with the validated Patient-Reported Outcomes Measurement Information System (PROMIS) outcome measures in patients with foot and ankle orthopaedic issues.…”
Section: Clinical Evaluation and Practicementioning
confidence: 97%
“…Comprehensive assessments addressing patients' experiences with the process and provision of health care have recently gained popularity; however, they have shown little association with PROMs [1,7,8,21,30]. Other than assessing global satisfaction and generic health-related quality of life (ie, not linked to a certain condition), there are no comprehensive assessments to capture how patients rate the impact of their spine condition on their overall health and well-being.…”
Section: Introductionmentioning
confidence: 99%